Online dating behaviours: an emerging reproductive health issues among undergraduates in Anambra State, Nigeria (2015)
This study examined the extent to which personality-type, self-esteem, parental socio-economic status and social network utilization predict online dating behaviours among university undergraduates in Anambra state. Multi-stage sampling technique was used to draw 1,007 respondents (Female=708; Male=299) with age range of 18 to 28 years (x = 17.08; SD= 6.01) from an estimated population of 10, 244 undergraduates in Anambra state universities. Four standardized scales and one researcher developed instrument were utilized. Results of Pearson Product Moment Correlation show that the hypothesized variables have significant positive relationship ranging from .86 to .36 at 0.05 level of significance (2-tailed). Regression Analysis indicates that the independent variables jointly accounted for 84% of the variance in the prediction of online dating behaviours of the respondents. However, parental socio-economic-status made the highest contribution (fi=.368; p< 0.05). The outcome suggests that dispositional and socioeconomic factors correlate with online dating behaviours of the respondents. Counsellors should leverage programme designers to ensure that techniques of identifying users’ profiles especially their personality traits are incorporated into web to enable potential online dates have compatible partners for meaningful and satisfying relationship.